Accountability, autonomy, and governance challenges of public university hospitals in Egypt - Badr, Yasmine (AUC Knowledge Fountain, 2017)
In Egypt, public university hospitals play a crucial role not only in education and research but also in the provision of healthcare services. What adds to the complexity of public university hospitals is their existence within two sectors; higher education and healthcare. This work highlights the inability of Egyptian public university hospitals to achieve their tripartite mission as a result of improper institutional governance arrangement that does not empower hospitals to cope with the requirements of both sectors. Despite the importance of institutional governance to university hospitals in Egypt, this topic remains under researched in the literature. This qualitative study aims to explore the existing institutional governance arrangement of public university hospitals in Egypt, identify key issue domains that they face and means to overcome these challenges, and the current reforms undertaken in public university hospitals. In-depth interviews are carried out with ten participants covering six different public university hospitals across Egypt selected purposively. Interviews range between 30-60 minutes each with subject-matter experts, top leaders/ managers in public university hospitals and medical schools, and representatives from regulatory bodies. The analysis of the study follows the framework for public hospital governance and the owner model of university hospital governance. Findings of this research reveal that public university hospitals follow the unified governance arrangement. It has a number of advantages such as easier agreement between clinical and academic enterprises, and alignment of academic plans with clinical training. Yet, there are associated problems with the existing governance arrangement manifested in the limited autonomy of university hospital managers, centralization of decision making at different organizational levels, financial mismanagement, and imbalance between academic and clinical endeavors in certain cases. The study recommends the continuation of the unified governance arrangement to university hospitals, yet with more autonomy to the dean, general manager of hospitals and hospital managers. The need to develop boards of directors professionally in terms of composition and size is crucial to the accountability of university hospitals. Hospital managers need to be adequately empowered in alignment with their clinical, administrative and financial responsibilities. Financially, all revenue streams need to be consolidated electronically and linked to the missions.